Integration of Fiqh Muamalah Teaching in Economic Education at Traditional Pesantren - Suadi, Suadi; Uddin, Md. Akther; Fathurrohman, Amang; Yusuf, Yusuf; Mukarromah, Neng (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2025)
Purpose: This study aims to analyze the integration of Fiqh Muamalah in economic education at Pondok Pesantren Sidogiri. It explores how Fiqh Muamalah teachings are applied in the context of Islamic economic education at a traditional pesantren. Methodology/Approach: The research was conducted at Pondok Pesantren Sidogiri located in Pasuruan. The study uses a field research approach with a qualitative descriptive design. Data collection techniques involved interviews, observations, and documentation. Results/Findings: The study found that Pondok Pesantren Sidogiri successfully integrates Fiqh Muamalah with Islamic economic education through collective ijtihad and integrative ijtihad approaches. The pesantren also applies Islamic principles in its pesantren cooperatives and sharia financial institutions, contributing to the economic empowerment of the community. Conclusion: The findings indicate that the integration of Fiqh Muamalah at Pondok Pesantren Sidogiri strengthens the role of pesantren not only as a center of Islamic scholarship but also as an institution for developing Islamic economic practices. By contextualizing classical teachings with contemporary issues, the pesantren provides a model of how traditional Islamic education can remain relevant and contribute to community-based economic empowerment. Limitations: This study is limited to one pesantren, so the findings may not fully reflect the practices of other pesantren. The use of a descriptive qualitative method means that broad generalizations cannot be made. Contribution: This study contributes to the development of Islamic economic education at pesantren and can serve as a reference for further research on the integration of Fiqh Muamalah in economic education at traditional pesantren.